2006
DOI: 10.1080/03008200600995908
|View full text |Cite
|
Sign up to set email alerts
|

BMP Stimulation of Alkaline Phosphatase Activity in Pluripotent Mouse C2C12 Cells is Inhibited by Dermatopontin, One of the Most Abundant Low Molecular Weight Proteins in Demineralized Bone Matrix

Abstract: Demineralized bone matrix (DBM) is a complex mixture of osteoinductive bone morphogenetic proteins (BMPs), as well as BMP-binding proteins that regulate BMP bioactivity and localization. Our aim was to use modern proteomic methods to identify additional BMP-binding proteins in DBM, with initial emphasis on the most abundant. Relatively large, water-soluble noncollagenous proteins (NCPs) were preferentially extracted from DBM with alkalinized urea. The insoluble residue, which contained the BMP activity, was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The solidus between names indicates alternate names or homologs in different species. a Reviewed by Garcia Abreu et al, 2002; reviewed by Gazzerro and Canalis, 2006; c reviewed by Balemans and Van Hul, 2002;d Vilmos et al, 2001;e Cowan et al, 2007;f Yanagita, 2005;g Yu et al, 2008;h Paine-Saunders et al, 2000;i Fujise et al, 2001;j Kirkpatrick et al, 2006;k Gumienny et al, 2007;l Fisher et al, 2006;m Moreno et al, 2005;n Ohta et al, 2004; o Kirkbride et al, 2008;p Fung et al, 2007;q Wilkinson et al, 2003;r Sieron et al, 2002;s Zhu et al, 1999;t Moser et al, 2003;u Serpe et al, 2008;v Lin et al, 2005;w Matsui et al, 2000;x Babitt et al, 2005;z Kanomata et al, 2009;aa Onichtchouk et al, 1999;bb Yao et al, 2008;cc Wallin et al, 2000;dd Brochmann et al, 2009;ee Behnam et al, 2006;ff Rittenberg et al, 2005;gg Szweras et al, 2002;hh Saito et al, 2008; ii Wang et al, 2008;jj Arteaga-Solis et al, 2001; kk Sengle et al, 2008a. REVIEW Development 136 (22) degradation of BMP-bound receptors; at present, no extracellular proteases that specifically target ligands of the transforming growth factor  (TGF) superfamily for destruction have ...…”
Section: Introductionmentioning
confidence: 99%
“…The solidus between names indicates alternate names or homologs in different species. a Reviewed by Garcia Abreu et al, 2002; reviewed by Gazzerro and Canalis, 2006; c reviewed by Balemans and Van Hul, 2002;d Vilmos et al, 2001;e Cowan et al, 2007;f Yanagita, 2005;g Yu et al, 2008;h Paine-Saunders et al, 2000;i Fujise et al, 2001;j Kirkpatrick et al, 2006;k Gumienny et al, 2007;l Fisher et al, 2006;m Moreno et al, 2005;n Ohta et al, 2004; o Kirkbride et al, 2008;p Fung et al, 2007;q Wilkinson et al, 2003;r Sieron et al, 2002;s Zhu et al, 1999;t Moser et al, 2003;u Serpe et al, 2008;v Lin et al, 2005;w Matsui et al, 2000;x Babitt et al, 2005;z Kanomata et al, 2009;aa Onichtchouk et al, 1999;bb Yao et al, 2008;cc Wallin et al, 2000;dd Brochmann et al, 2009;ee Behnam et al, 2006;ff Rittenberg et al, 2005;gg Szweras et al, 2002;hh Saito et al, 2008; ii Wang et al, 2008;jj Arteaga-Solis et al, 2001; kk Sengle et al, 2008a. REVIEW Development 136 (22) degradation of BMP-bound receptors; at present, no extracellular proteases that specifically target ligands of the transforming growth factor  (TGF) superfamily for destruction have ...…”
Section: Introductionmentioning
confidence: 99%
“…Most convincingly, DPT modulates cell behavior indirectly by modulating cell-ECM interactions [1], DPT binds several known growth factors including TGFβ and BMP2 [3,4], altered DPT expression is observed during tissue injury [28][29][30][31][32][33], and DPT knockout mice only show subtle changes to skin elasticity [7]. In addition, Okamoto & Fujiwara suggest that DPT contributes predominately to matrix remodeling during wound healing and that further studies on wound healing in DPT transgenic mice mayeluci date the specific roles of DPT in response to injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…Dermatopontin (DPT) is a 22-kDa tyrosine-rich extracellular matrix (ECM) protein that is found at high levels in demineralized bone matrix and cartilage and may play an important role in skeletal tissue function [1][2][3]. It is thought that DPT acts largely as a mediator between the cell and the ECM environment [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using LC-MS/MS authors identified this factor as BMP4, and found it to be in over 100 kDa complex in circulation. Behnam et al (2006) identified dermatopontin (DPT) as the most prominent BMP-2 co-purified demineralized bone matrix protein, using alkaline urea extraction of BM, separation of insoluble fraction by hydroxyapatite chromatography, SDS-PAGE of BMP active fraction and MALDI-TOF analysis. Kubota et al (2002) have studied signal transduction from osteoclasts to osteoblasts.…”
mentioning
confidence: 99%